ADMISSION-ORIENTATION MODEL AT PURWOKERTO CLASS IIA CORRECTIONAL FACILITY - Indrajanus, Aziz; Yuska, Syahrial (Universitas Nusa Cendana, 2025)
The Class IIA Purwokerto Correctional Facility (Lapas) implements the Admission-Orientation Period (Mapenaling) program as an effort to help inmates adapt to the new environment and prevent violations during their imprisonment. Mapenaling plays an important role in the initial rehabilitation of inmates, but its implementation often faces challenges that affect the effectiveness of the program. This study aims to analyze the implementation of Mapenaling at the Class IIA Purwokerto Correctional Facility and identify the factors that hinder its success. This research uses a qualitative method with a case study approach. Data were collected through observations, in-depth interviews with correctional officers and inmates, and analysis of related documents. The results of the study indicate that there are discrepancies between the implementation of Mapenaling and the established standard operating procedures. Some of the main obstacles include the lack of training and understanding of the Mapenaling material among officers, time constraints, and inadequate resources. As a result, the program has not fully succeeded in shaping inmate behavior in accordance with the rehabilitation goals. The conclusion of this research underscores the need for improvements in the implementation of Mapenaling, including increased training for officers and adjustment of procedures to be more relevant to field conditions. It is hoped that with evaluation and adjustments, Mapenaling can become a more effective instrument in the inmate rehabilitation process at the Class IIA Purwokerto Correctional Facility. Keywords: Admission-Orientation Period; Mapenaling; Inmate Adaptation; Officer Training; Implementation Challenges